Identification and characterization of tak1 regulated signaling pathway - Xi, Jia Jia (2012)
TGF β-activated protein kinase 1---TAK1 has been reported for its roles in mediating stimulation of LPS and proinflammatory cytokines, activating of NFκB and mitogen activated protein kinase (MAPK) as well as regulating cellular response to reactive oxygen species (ROS) and hyperosmotic stress. The precise regulation of TAK1 signaling pathway in various physical conditions is critical for cells to coordinate appropriate cellular responses. mTOR pathway is one of the most important regulatory machineries of cell growth. In this study, we spare no effort to investigate the molecular connections between inflammatory signals and mTOR pathway. The switch of mTOR pathway---TSC2 is identified as binding partner of TAK1 by IP-MS approach, which is confirmed by IP/IB approach. Phosphorylation of TSC2 on Thr1462 is detected upon LPS/TNFα/IL-1β stimulations. TAK1 mediated phosphorylation on Ser1365 of TSC2 is identified by MS. The phosphorylation of TSC2 leads to activation of mTOR pathway, indicated by phosphorylation of p70S6K1 on Ser389 and 4EBP1 on Thr70, which is associated by TAK1 kinase activity. Suppression of expression of TAK1 attenuated activation of mTOR pathway upon LPS and TNFα stimulations. Inhibition of TAK1 kinase activity by chemical inhibitor and genetic modification led to the reduced mTOR response towards stimulations. These data drive us to the conclusion that TAK1 phosphorylates TSC2 to activate mTOR pathway, which subsequently regulates cellular responses to LPS, TNFα and IL-β stimulations. We also characterize regulation of TAK1 signaling pathway mediated by HIPK2. We propose that HIPK2 negatively regulates TAK1 signaling pathway by interrupting the polyubiquitin binding of TAB2/TAB3 upon LPS, TNFα and IL-1β stimulations.